A practice-centered analysis of environmental accounting standards: integrating agriculture into carbon governance. (July 2020) - Wolf, Steven A.; Ghosh, Ritwick
Highlights: Carbon accounting is at the core of carbon governance. There is a need to study carbon standard making as practically and situationally performed. In practice, carbon standards are a product of negotiation, deliberation, and compromise. Relevance of carbon accounting within the broader project of enlisting agriculture in carbon markets is assessed. Abstract: Standards for carbon accounting are a core element of environmental governance. We study the production of standards as situated and practical action, which is shaped by opportunities, resource constraints, and existing infrastructure. Careful observations of this work reveals what people do and how they organize their actions relevant to the particular questions, conventions, and resources at hand. We apply this practice-centered, ethnomethodological approach to study the creation of an accounting protocol for nitrous oxide emissions from corn production, an effort within the broader project of enlisting agriculture in carbon markets. We find that efforts to create a far-reaching, rigorous, and efficient standard were frustrated by lack of data, contestation of knowledge claims, and the challenges of collapsing real-world heterogeneity into a model and a set of tidy decision rules. In this sense, carbon accounting standards should be understood as provisional, and potentially unstable, compromises.